Meningkatkan Motivasi Belajar Secara Online Selama Masa Pandemi Covid 19 Pada Asrama Yatim Dan Duafa Kafilatiur Rosul Di Pamulang - Amirudin; Ade Yusuf; Nurmono (CV. Multi Kreasi Media, 2023)
Community service activities carried out by a team of lecturers from the Management Study Program at Pamulang University (Unpam) in 2021, are community service activities that focus on motivating the Orphan Dormitory and Duafa Kafilatur Rosul. This activity was divided into 2 stages, namely the first stage in the form of exposure to online learning motivation material and the second stage in the form of discussions, questions and answers and sharing with the Orphans and Duafa Dormitory Kafilatur Rosul about the obstacles to online learning with the results of the activities that have been carried out, obtained the result is that as many as 69% of the Orphans and Duafa Dormitories Kafilatur Rosul, both in terms of understanding and support such as media (gadgets and credit/wifi). With this activity it is hoped that the students will have the enthusiasm to continue learning even though it is online.